論攝影著作之原創性 - 黃心怡(Serena Shin-Yi Huang) (東吳法律學報, 2013)
In Taiwan, courts and scholars have controversies over the level of the creativity required in determining the originality of photographic works. Therefore, there are inconsistent court decisions regarding the originality of photographic works, especially photographic renditions. This article analyzes the current originality standards of photographic works applied by Taiwan courts and relevant decisions reached by US courts and suggests different standards of originality for different types of photographic works.